Distribusi Suhu Permukaan Tanah dan Hubungannya Indeks Vegetasi di Hutan Pinus Lahendong - Novanda Tamboto; Cyrke Adfie Netty Bujung; Jeane Cornelda Rende (Jurnal FisTa : Fisika dan Terapannya, 2023)
Pine Forest is a mountain located in North Sulawesi Province, Indonesia. The surface temperature around the Pine Forest changes from year to year. Whether the changes occurred significantly or only slightly, it certainly had an effect on the vegetation around the mountain. The purpose of this study was to determine the surface temperature and vegetation in the geothermal manifestation area around the Pine Forest based on the Remote Sensing Method. By using remote sensing can calculate the vegetation and surface temperature in the Pine Forest. In this study, the analysis uses Landsat 8 satellite imagery in 2020. According to the results, vegetation is negatively correlated with surface temperature, which means that vegetation and surface temperature are inversely correlated. The higher the vegetation, the lower the surface temperature value and vice versa, the higher the surface temperature, the lower the vegetation index.